Blunt Trauma Associated With Bilateral Diaphragmatic Rupture: A Case Report - Pace, Marco; Vallati, Damiano; Belloni, Elena; Cavallini, Marco; Ibrahim, Mohsen; Rendina, Erino Angelo; Nigri, Giuseppe (Frontiers in Surgery, 2021)
Background: A bilateral diaphragmatic rupture is a rare event that occurs in cases of blunt thoracic-abdominal trauma. Case Presentation: We report the case of a 56-year-old female patient with pelvic fracture and second-stage bilateral rupture of the diaphragm due to a car accident. After a chest and abdominal contrast-enhanced computed tomography (CT) scan, the patient underwent emergency suturing of the left hemidiaphragm. On postoperative day (POD) 4, a CT scan performed due to the sudden onset of dyspnea revealed rupture of the right hemidiaphragm, which was not detected on the preoperative CT scan. On POD 9, the right hemidiaphragm was repaired with mesh during a right thoracotomy. The patient recovered 14 days after surgery. However, the postoperative course was complicated by an asymptomatic COVID-19 infection that significantly delayed her discharge from the hospital. Conclusions: Difficulties in preoperative diagnosis and treatment, together with the lack of data in the literature, make this type of trauma a challenge for all acute care and general surgeons.